Malaysian cultural differences in knowledge, attitudes and practices related to erectile dysfunction: focus group discussions. - Low, W.Y.; Wong, Y.L.; Zulkifli, S.N.; Tan, H.M. (Nature Publishing Group, 2002)
This qualitative study aimed to examine cultural differences in knowledge, attitudes and practices related to erectile dysfunction (ED) utilizing focus group discussion. Six focus groups consisting of 66 men, 45-70-y-old were conducted-two Malay groups (n=18), two Chinese groups (n=25) and two Indian groups (n=23). Participants were purposely recruited from the general public on a voluntary basis with informed consent. Transcripts were analyzed using qualitative data analysis software ATLASti. The Malay and Chinese traditional remedies for preventing or treating ED are commonly recognized among all races. Many have a negative perception of someone with ED. Malay and Chinese men tended to blame their wife for their problem and thought that the problem might lead to extra-marital affairs, unlike the Indian men who attributed their condition to fate. Malays would prefer traditional medicine for the problem. The Chinese felt they would be more comfortable with a male doctor whilst this is not so with the Malays or Indians. Almost all prefer the doctor to initiate discussion on sexual issues related to their medical condition. There is a need for doctors to consider cultural perspectives in a multicultural society as a lack of understanding of this often contributes to an inadequate consultation.